How to invest when you don't have any money : the fool's guide - Spink, Christopher (Boxtree London, 2000)
the book "How to Invest When You Don't Have Any Money: The Fool's Guide" by Chris Spink, published in 2000. This 192-page paperback, part of the Motley Fool series, offers practical advice on personal finance and investing, tailored for individuals with limited financial resources. The book is known for its accessible and humorous approach to demystifying investment concepts. Given its publication date, the book provides historical context up to the early 2000s. For more recent information on investing strategies and personal finance, additional sources would be beneficial.